Gamma-Aminobutyric Acid Transaminase (GABA-T) Deficiency in a Consanguineous Saudi Family: A Case Report and Literature Review - Kentab, Amal Y. (Journal of Pediatric Epilepsy, 2022)
Gamma-aminobutyric acid transaminase (GABA-T) deficiency is a rare, autosomal recessive disorder caused by mutations in the 4-aminobutyrate aminotransferase (ABAT) gene, which encodes an enzyme involved in GABA catabolism. It is characterized by severe psychomotor retardation, early-onset epileptic encephalopathy, intractable seizures, hypotonia, hyperreflexia, movement disorder, hypersomnolence, and early childhood mortality. It is associated with elevated free GABA in cerebrospinal fluid (CSF), GABA-T deficiency in cultured lymphoblasts, hypomyelination on brain magnetic resonance imaging (MRI), and elevated GABA level in the basal ganglia on proton magnetic resonance spectroscopy (MRS). Only 14 cases have been published in the literature. A rare case of infantile epileptic encephalopathy caused by GABA-T deficiency resulting from a previously unreported homozygous missense mutation in the ABAT gene is described. Our findings add to the phenotypic, neuroradiological, and genetic spectrum of ABAT mutations.
Keywords: GABA-T deficiency; 4-aminobutyrate aminotransferase; ABAT gene; MRI